Gen Z Muslims, Social Contestation, and Digital Citizenship in Indonesia - Wildan, Mursyidul; Pratama, Imam Alfikri; Sugiarto, Dody (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2025)
This study aims to analyze the contestation, patterns, and forms of social movements among Gen Z Muslims in the era of digital citizenship. In this era, social movements are shaped by issue-based networks, and the key actors driving this transformation are Gen Z activists—particularly Muslim university students affiliated with Islamic student organizations. This article focuses on two main objectives: (1) to analyze the social contestation of Gen Z Muslim movements in the digital citizenship era and (2) to examine the patterns and forms of these movements in relation to their religious identity. This study employs a qualitative research method, with research subjects drawn from Islamic student organizations in Bandung and Pangkalpinang. Data collection techniques include: first, interviews, which were conducted to explore participants' perspectives on the ideology and activities of their movements; second, participatory observation, used to understand internal dynamics, patterns of interaction, and activism practices among Gen Z Muslims; and third, social media observation, utilized to analyze datasets from online platforms. The findings reveal two main categories of Gen Z Muslim social movements in the digital citizenship era: moderate and non-moderate. Moderate movements primarily focus their digital activism on issues of religious tolerance, inclusivity, interfaith dialogue, social justice, gender equality, and minority rights. In contrast, non-moderate movements center their activism on exclusive and conservative religious discourse, often using hashtags such as #Khilafah and #Hijrah as part of their outreach. These movements also tend to idolize figures advocating for religious purification and hijrah (religious migration). Furthermore, the patterns and forms of Gen Z Muslim social movements in the digital citizenship era are characterized by two key practices: volunteerism and crowdfunding, both of which serve as mechanisms for social engagement and mobilization.